KARAKTERISTIK MEKANIK KELONGSONG BAHAN BAKAR NUKLIR TEMPERATUR TINGGI DALAM ATMOSFER GAS NITROGEN - Sigit, Rohmad; Ismarwanti, Sri; Guswardani; Susanto, Yatno Dwi Agus; Setiawan, Jan (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
At Loss of Cooling Accident (LOCA) scenario, Zr-2 and Zr-4 as nuclear fuel cladding potentially exposed to air which experimentally leads to mechanical properties degradation faster than in steam environment. This study aims to determine the impact of nitrogen on the mechanical strength of cladding by minimizing other environmental influences. The Zr-2 and Zr-4 cladding was annealed under vacuum at a temperature of 500°C for one hour. It was followed by nitriding with the pressure of 1500 mbar for two hours. It was followed by natural cooling to room temperature. The results of tensile strength and microhardness testing showed that tensile strength, ductility and microhardness values increase of 12.1%, 19.2% and 28.2% for Zr-2 and 5.1%, 25% and 22.6% for Zr-4, respectively. Nitride layer was formed on the cladding surface due to interaction with nitrogen and there is no mechanical properties degradation due to nitriding process. It was caused by nitriding processes that were not followed or accompanied by oxidation processes.